A panorama of statistics : perspectives, puzzles and paradoxes in statistics - Sowey, Eric (John Wiley & Sons, Ltd, 2017)
Lending itself equally to reading through and to dipping into, this lively and inviting book will surprise teachers, students and practitioners by the variety of ways in which statistics can capture and hold their interest. --